1998
DOI: 10.1038/sj.onc.1201981
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB by oncogenic Raf in HEK 293 cells occurs through autocrine recruitment of the stress kinase cascade

Abstract: Raf-1 kinase has been implicated in the induction of NFkB activity by serum growth factors, phorbol ester and PTK oncogenes. Here we show that Raf activation of NF-kB, as measured in reporter gene assays, occurs indirectly and requires the stress kinase cascade. The stress pathway presumably becomes activated through induction of an autocrine loop by activated Raf (Raf-BXB) as suramin, the tyrphostin AG1478 and a dominant negative mutant of the EGF-R blocked NFkB activation. Raf-BXB synergizes with SAPKs and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…46,47 Alternatively, ERK and PI3K/ Akt may act as a parallel signaling pathway, and the autocrine or paracrine secretion of growth factor presumably is involved. 74,75 In conclusion, results from this report show that aggretin elicits HUVEC proliferation and migration and promotes angiogenesis in vivo and in vitro. According to the flow cytometric binding assay, ␣ 2 integrin, but not GPIb or ␣ v ␤ 3 receptor, is the major endothelialbinding site.…”
Section: Discussionmentioning
confidence: 83%
“…46,47 Alternatively, ERK and PI3K/ Akt may act as a parallel signaling pathway, and the autocrine or paracrine secretion of growth factor presumably is involved. 74,75 In conclusion, results from this report show that aggretin elicits HUVEC proliferation and migration and promotes angiogenesis in vivo and in vitro. According to the flow cytometric binding assay, ␣ 2 integrin, but not GPIb or ␣ v ␤ 3 receptor, is the major endothelialbinding site.…”
Section: Discussionmentioning
confidence: 83%
“…Another study showed that a mutation in the Raf-1 protein (T481A) that disrupts its ability to bind to MEK1 is still able to activate NF-B reporters (Pearson et al, 2000). In addition, two reports indicate that Raf-1-dependent activation of NF-B involves autocrine signaling either through interleukin-1 (Vale et al, 2001) or EGF receptor signaling (Troppmair et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Ras activates MAPK signaling cascades that most likely include the small GTP-binding protein Rac and the MEKK, PAK, and MKK4/SEK1 kinases. MKK4/ SEK1 can activate both the JNK and p38 (Troppmair et al, 1998). Therefore, we cannot exclude the possibility that p38 and/or JNK are activated through other Rasactivated pathways, including Rac, PI3K, or MKK4/ SEK.…”
Section: B-------------------------------------------------mentioning
confidence: 99%